The Effect of the "Woman Life Freedom" Protests on Life Satisfaction in Iran: Evidence from Survey Data - Mohammad Reza Farzanegan; Sven Fischer (Center for Economic Studies and ifo Institute (CESifo), 2023)
This study examines the causal effect of the violent "Woman, Life, Freedom" protests in Iran during the last quarter of 2022 on individual life satisfaction. To evaluate the impact, we use two original representative surveys in Iran conducted in 2022. Our results, based on an ordered logit regression analysis for a sample of more than 2,000 individuals, show that the violent protest environment had a significant and negative effect on life satisfaction in Iran. To determine the exposure of the respondents to protests, we calculated the number of protests within a 25km radius of the respondents' locations. The protest environment reduced the probability of life satisfaction by 3.7 percentage points. Moreover, we find significant heterogeneity among the respondents with respect to their life satisfaction before and after protests. The largest negative impact of the protests on life satisfaction is observed among women, members of working class, and those with primary and tertiary education. These results are robust to other determinants of individual life satisfaction, such as marital status, employment, perception of corruption, feeling of security, religiosity, and other sociodemographic factors.
Keywords: D74; F52; H56; I31; N15; 330; protest; violence. life satisfaction; well-being; Woman Life Freedom; survey; Iran